Medical dispensation in La Rioja, Spain: epidemiology and its relationship with social determinants: a descriptive study - Aparicio-Rodríguez, Gonzalo; Juárez-Vela, Raúl; Burgos-Esteban, Amaya; Sancho-Sánchez, Consuelo; Santos-Sanchez, José Ángel; Navas-Echazarreta, Noelia; Cobos-Rincón, Ana; Cardoso-Muñoz, Antonio; Ruiz de Viñaspre-Hernández, Regina; Larrayoz, Ignacio M. (Frontiers in Pharmacology, 2025)
IntroductionSpain stands out as the European Union country with the highest life expectancy, reaching 83.2 years in 2022. This context is accompanied by population aging and an increase in chronic and degenerative diseases, which translates into greater medication use. In 2022, the National Health System (NHS) dispensed over 1,127.8 million packages. This study aims to evaluate the state of medication dispensation in La Rioja and its relationship with health determinants such as economic conditions, area of residence, age, and gender.MethodsWe conducted an observational, retrospective, cross-sectional study between January 2016 and December 2023. A total of 4,108,656 raw e-dispensations (2016–2023) were recorded, from which 1,433,531 unique patient–ATC4–year records (26 frequent subgroups) were analyzed. We included patients aged 14 years and older with electronic dispensations. Variables analyzed included age, gender, socioeconomic level, type and number of dispensations, and the patient’s basic health zone. Statistical analyses employed Chi-square tests for categorical associations and Kruskal–Wallis tests to compare age distributions across ATC4 medication groups, with a significance level of p < 0.05.ResultsProton pump inhibitors (PPIs) were the most dispensed medications in La Rioja, with 82,195 dispensations between 2016 and 2023, followed by propionic acid derivative anti-inflammatory drugs. Antidepressant dispensations increased from 5,281 in 2016 to 7,486 in 2023. Regarding gender differences, women accounted for more dispensations (53.7%). The largest differences favoring women were observed in thyroid hormones, vitamin D, and antidepressant groups. Conversely, medication groups indicated for cardiovascular pathology—such as platelet aggregation inhibitors and angiotensin-converting enzyme inhibitors—showed a significant difference favoring men. Among the elderly, the most dispensed medications also corresponded to families indicated for cardiovascular diseases. By health zones, PPI dispensation was high and homogeneous in the Rioja 1 and Rioja 2 clusters, while anxiolytics and antidepressants stood out in the municipality of San Román and the Guindalera area of Logroño. In socioeconomic terms, pensioners with limited incomes (IHC 002) primarily consumed PPIs, paracetamol, and benzodiazepines, while low-income workers (IHC 003) showed notable dispensation of propionic acid derivatives, PPIs, and paracetamol.DiscussionOur findings align with national and European trends: PPIs and propionic acid derivative anti-inflammatories are the most frequently dispensed medications. Between 2016 and 2023, we observed an increase in the absolute number of unique users in ATC4 subgroup N06AX (Other antidepressants) (+41.8%) and, to a lesser extent, in N06AB (Selective serotonin reuptake inhibitors) (+25.5%), while the annual relative share of N06AB remained essentially stable. Socioeconomic determinants—such as low income and unemployment—appear to directly influence access to and dispensation of medications.ConclusionMedication dispensation patterns in La Rioja mirror broader national and EU trends, with PPIs and propionic acid derivatives leading. Gender, age, geographic zone, and socioeconomic status are associated with distinct dispensation profiles. Targeted public health strategies should consider these determinants to optimize rational medication use and equity in access.